A Simulation Based Study on Inter-VLAN Routing - Somasundaram, S; Chandran, M (International Journal of Computer Sciences and Engineering, 2025)
The VLAN technology is a technology which is used to logically divide the network into different broadcast domains. So that the packets are delivered within the port of same VLAN group. According to this paper the VLAN is the basis of the Inter-VLAN connection. Inter-VLAN routing technique is a technique which is used to allow different VLANs to communicate. In order to communicate we make use of router interface or multilayer switches. We have implemented this Inter-VLAN routing concepts using Packet Tracer Tool 6.0.1.